Pre Calculus

Simplify the expression. 9 log 9 2

This is 9 to the power of log base 9 of 2

a. 2
b. 18
c. 4
d. 9
e. none of these

  1. 👍
  2. 👎
  3. 👁

Respond to this Question

First Name

Your Response

Similar Questions

  1. Trigonometry

    This is a logs question If u=x/y^2, which expression is equivalent to log u? 1) log x + 2 log y 2) 2(log x- log y) 3) 2(log x + log y) 4) log x- 2 log y

  2. Trigonometry

    The expression log(x^n/ radical y)is equivalent to 1. n log x - 1/2 log y 2. n log x- 2 log y 3. log (nx) - log (1/2y) 4. log (nx) - log (2y)

  3. chemistry

    Q: Calculate the pH of a solution that is 0.56 M HC3H5O3 and 1.28 M NaC3H5O3. I used the H-H equation for this and got this so far: HC3H5O3 acid NaC3H5O3 base pH = pKa + log([NaC3H5O3]/[HC3H5O3]) = -log(Ka of HC3H5O3) +

  4. math(Please help)

    1) use the properties of logarithms to simplify the logarithmic expression. log base 10 (9/300) log - log 300 log 9 = 2 log 3 log 300 = log 3 + log 100 = log 3+2 I just do not know how to put these together now!

  1. pre calculous

    use the properties of logarithms to write the expression as a sum or difference of logarithms or multiples of logarithms. show your work ln x^2/y^3 Assuming x,y AND z are positive use properties of logariths to write the

  2. Algebra 2

    How is the expression log 32 - log 8 written as a single logarithm? log 4 log 8 log 24 log 40

  3. Math

    If ln a=2, ln b=3, and ln c=5, evaluate the following: (a) ln(a^−2/b^4c^−3)= -.9524 (b) ln(√b^−4*c^1*a^−1)= -1.739 (c) ln(a^2b^4)/ln(bc)^−2= 42.39 (d) (ln(c^−1))*(ln(a/b^3))^−4= -.03507 I am getting these answers

  4. logarithm functions

    use the properties of logarithms to expand the expression as sum, difference or multiple of logarithms. Simplify. a.log(x^3/2) b.log base4 16a

  1. Math/trig

    Log radical b/ a^2 is equivalent to 1) 1/2 log b + 1/2 log a 2) l/2 log b- 2 log a 3) 2 log b - 1/2 log a 4) 1/2logb/2 log a

  2. math

    Given that 2 log base2 (x+15) - log base2 x = 6 1.Show that x^2 -34x +225 = 0 2. Hence or otherwise solve the equation 2 log base 2 (x+15) - log base 2 x =6

  3. Math

    solve log(7x-3)+2log(5)=2+log(x+3) I've attempted to do this question and I ended up with log(7-3)+log(5^2)-log(x+3)=2 but I don't what to do next or whether I did something wrong.

  4. math

    mathematically Evaluate without using tables 2 log base 10 raised 2 power 5 + log base 10 36 - log base10 9 that is, 2log10 5 +log 10 36 - log 10 9

You can view more similar questions or ask a new question.